Alterations of a spectrum of driver genes in female Chinese patients with advanced or metastatic squamous cell carcinoma of the lung. Issue 2 (February 2015) - Qiong, Zhao; Na, Wang Yi; Bo, Wang; Zhu, Zeng; Ling, Peng; Bo, Mou Hai; Min, Tang Ye; Lei, Zeng; Na, Hu Dan; Bo, Zhao; Fang, Liu Jun; Seng, Zheng Shu
Highlights We analyzed molecular abnormalities in Chinese females with advanced SQCLC. Three specificities of female SQCLCs were observed: less smoking history, younger age and more peripheral type. No significant differences in EGFR, KRAS, EML4-ALK, PTEN and FGFR1 between different genders were found. Significant lower frequency of PIK3CA mutation was detected in females.